JNK phosphorylation and activation of BAD couples the stress-activated signaling pathway to the cell death machinery. - Donovan, N; Becker, E; Konishi, Y; Bonni, A (2002)
The c-Jun N-terminal kinase (JNK) signaling pathway plays a critical role in mediating apoptosis in the developing and mature organism. The JNK signaling pathway is thought to induce apoptosis via transcription-dependent and transcription-independent mechanisms that remain to be elucidated. In this study, we report a novel mechanism by which the JNK signaling pathway directly activates a component of the cell death machinery. We have found that JNK catalyzes the phosphorylation of the BH3-only protein BAD at the distinct site of serine 128 in vitro. Activation of the JNK signaling pathway induces the BAD serine 128 phosphorylation in vivo, including in primary granule neurons of the developing rat cerebellum. The JNK-induced BAD serine 128 phosphorylation promotes the apoptotic effect of BAD in primary neurons by antagonizing the ability of growth factors to inhibit BAD-mediated apoptosis. These findings indicate that BAD is a novel substrate of JNK that links the stress-activated signaling pathway to the cell death machinery.